2021
DOI: 10.21203/rs.3.rs-846238/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Entropic Associative Memory for Manuscript Symbols

Abstract: Manuscript symbols can be stored, recognized and retrieved from an entropic digital memory that is associative and distributed but yet declarative; memory retrieval is a constructive operation; symbols not contained in the memory are rejected directly without search; and memory operations can be performed through parallel computations. Manuscript symbols, both letters and numerals, are stored in Associative Memory Registers that have an associated entropy. The memory recognition operation obeys an entropy trad… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 27 publications
(53 reference statements)
0
2
0
Order By: Relevance
“…The Entropic Associative Memory (EAM) 1,2 is a novel declarative but distributed model of associative memory. EAM consists on a set of Associative Memory Registers (AMRs) implemented as finite bi-dimensional arrays or tables.…”
Section: Entropic Associative Memorymentioning
confidence: 99%
See 1 more Smart Citation
“…The Entropic Associative Memory (EAM) 1,2 is a novel declarative but distributed model of associative memory. EAM consists on a set of Associative Memory Registers (AMRs) implemented as finite bi-dimensional arrays or tables.…”
Section: Entropic Associative Memorymentioning
confidence: 99%
“…In the basic scenario, each AMR holds the representation of a set of objects of the same class. In previous work we used ten AMRs for holding the representations of the ten digits 1 ; and 47 AMRs for holding the representations of capital and lower case letters and digits 2 . We also showed that AMRs can hold representations of more than one class of objects simultaneously, with satisfactory precision and recall, but a moderate increase of the entropy.…”
Section: Entropic Associative Memorymentioning
confidence: 99%